Deradikalisasi bagi Generasi Muda Bandar Lampung Sebagai Antisipasi Perkembangan Radikalisme di Media Sosial - Karisma, Gita; Rachmawati, Tety; Inayah, Astiwi (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2024)
The ease of accessing information through social media is a challenge for the younger generation. One of the values that is easily accessible on social media is the value of radicalism. Radicalism is an attitude that wants fundamental transformation through violence. The young generation may access radicalism values easily that are often spread through social media platforms. Social media is used by radicalism actors for channeling ideas and recruiting media. Furthermore, Extreme radicalism potentially evokes a terrorism. This service aims to prevent radicalism, especially on social media, through deradicalization with the younger generation as the target participants. The method of socialization was implemented in this activity through explanation and discussion about tips on detecting radicalization and deradicalization through contents of counter radicalism on social media. These activities were closed by playing a game “Cinta Tanah Air”. The participants were young generation from various student organizations which located in Bandar Lampung such Himpunan Mahasiswa Jurusan (HMJ), Himpunan Mahasiswa Islam (HMI), Forum Studi Pengembangan Islam (FSPI), Ikatan Mahasiswa Muhammadiyah (IMM), Association Internationale Des Étudiants en Sciences Économiques et Commerciales (AISEC), UIN Raden Intan, Pusat Informasi dan Konseling Remaja (PIK-R), dan Badan Eksekutif Mahasiswa (BEM) Unila. This service has encouraged participants to be able to explain radicalism and deradicalization through counter-content as an effort to prevent radicalism. It could be seen from the post test results showing that about 92% of participants could understand and explain the various contents of counter radicalism on social media.